THE ROLE OF TECHNOLOGY IN EDUCATION - Asliddinov Shahobiddin Qahramon o‘g‘li, (TADQIQOTLAR, 2026)
Abstract. This article discusses the importance of modern technologies in the educational process and their impact on improving the quality of teaching and learning. The study analyzes the role of digital tools, online platforms, multimedia resources, and  interactive  teaching  methods  in  developing  students’  knowledge,  independent learning skills, and motivation. Special attention is paid to the use of technology in English  language  teaching  at  vocational  schools.  The  article  also  highlights  the advantages  and  challenges  of  technology-based  education  and  provides recommendations for effective implementation in classrooms.